Conversion of cycloalk-2-enones into 2-methylcycloalkane-1, 3-diones—assessment of various Tamao-Fleming procedures and mechanistic insight into the use of the Me3SiMe2Si unit. Issue 5 (22nd December 2015) - Yu, Guojun; Clive, Derrick L. J.
Abstract : 2-Methyl cycloalkane-1, 3-diones can be made by conjugate addition of Me3 SiMe2 SiLi to cycloalk-2-en-1-ones, ketalization, Tamao–Fleming oxidation (Bu4 NF, then H2 O2, KHCO3 ), TPAP oxidation and acid hydrolysis. Abstract : Conjugate addition of Me3 SiMe2 SiLi to cycloalk-2-en-1-ones, ketalization, Tamao–Fleming oxidation (Bu4 NF, then H2 O2, KHCO3 ), TPAP oxidation and acid hydrolysis generates 2-methyl cycloalkane-1, 3-diones. Ketalization is needed in order to prevent addition of Me3 Si − to the carbonyl. The pentamethyldisilanyl group has advantages over other silicon units that are used in Tamao–Fleming procedures.